(untitled) (Research, Society and Development, 2021)
This study aimed to verify the research participants’ perceptions regarding the feasibility and the perceived difficulty level of difficulty found in relation to the introduction of computational thinking (CT) in basic education, through the performance of unplugged activities. For this, the research participants, Pedagogy students, PIBID scholarship holders, and the supervising teachers, received training to know the pillars of computational thinking (decomposition, pattern recognition, abstraction and algorithms). In addition, they performed five unplugged activities, which they could apply to their students in the schools where they work. Methodologically, qualitative research was performed, based on data collection through the questionnaire instrument, aligned with methodological aspects of the Content Analysis proposed by (Bardin, 2016). The (BNCC) Common National Curriculum Base (BRASIL, 2017), foresees the use of the concepts of the CT to help the problem-solving processes, which shows the importance of the present study. This research contributes to teacher training by subsidizing the methodological practice of the supervising professor and the PIBID scholarship holder. The result of the application of the activities performed by the supervising teachers, with the help of the scholarship students, demonstrated the effectiveness of the work with the CT at school.